Feeding broilers with wheat germ, hops and grape seed extract mixture improves growth performance - Zou, Qiangqiang; Meng, Weishuang; Li, Chunxiao; Wang, Tieliang; Li, Desheng (Frontiers in Physiology, 2023)
In the study, Wheat germ, Hops and Grape seed extracts were made into a mixture (BX). The BX was supplemented in AA+ broilers diets to investigate the effects of BX on broiler growth performance, blood indicators, microbiota and noxious gas emissions in faeces. Four hundred and eighty 1-day-old AA+ male broilers with an average initial body weight (44.82 ± 0.26) were randomly divided into 4 dietary treatments of 6 replicates each, with 20 birds per replicate. The experimental groups consisted of a group fed a basal diet and groups fed basal diet supplemented with 0.05, 0.1 and 0.2% BX. The trail was 42 days. The results showed that supplementing the dietary with graded levels of BX linearly increased ADG and ADFI from days 22-42 and 1-42. When dietarys supplemented with 0.2% BX significantly increased ADG and ADFI on days 22-42 and 1-42 (P < 0.05). The addition of BX reduced H2S and NH3 emissions in the faeces; the levels of E. coli and Salmonella in the faeces were significantly reduced and the levels of Lactobacillus were increased (P < 0.05). In this trial, when the diet was supplemented with 0.2% BX, faecal levels of E. coli and Salmonella were consistently at their lowest levels and Lactobacillus were at their highest. At the same time, NH3 and H2S emissions from broiler faecal also had been at their lowest levels. Conclusion: Dietary supplementation with a 0.2% BX could improve the growth performance of broilers and also reduced faecal H2S and NH3 emissions, as well as faecal levels of E. coli and Salmonella, and increased levels of Lactobacillus. Thus, BX made by Wheat germ, Hops and Grape seed extract is expected to be an alternative to antibiotics. And based on the results of this trial, the recommended dose for use in on-farm production was 0.2%.